Science and fiction in critical care: established concepts with or without evidence? - Martin Westphal (Critical Care, 2019)
Abstract In the absence of evidence, therapies are often based on intuition, belief, common sense or gut feeling. Over the years, some treatment strategies may become dogmas that are eventually considered as state-of-the-art and not questioned any longer. This might be a reason why there are many examples of “strange” treatments in medical history that have been applied in the absence of evidence and later abandoned for good reasons. In this article, five dogmas relevant to critical care medicine are discussed and reviewed in the light of the available evidence. Dogma #1 relates to the treatment of oliguria with fluids, diuretics, and vasopressors. In this context, it should be considered that oliguria is a symptom rather than a disease. Thus, once hypovolaemia can be excluded as the underlying reason, there is no justification for giving fluids, which may do more harm than good in euvolaemic or hypervolaemic patients. Similarly, there is no solid evidence for forcing diuresis by administering vasopressors and loop diuretics. Dogma #2 addresses the treatment of crush syndrome patients with aggressive fluid therapy using NaCl 0.9%. In fact, this treatment may aggravate renal injury by iatrogenic metabolic acidosis and subsequent renal hypoperfusion. Dogma #3 concerns the administration of NaCl 0.9% to patients undergoing kidney transplantation. Since these patients are usually characterised by hyperkalaemia, the potassium-free solution NaCl 0.9%, containing exclusively 154 mmol/l of sodium and chloride ions each, is often considered as the fluid of choice. However, large volumes of chloride-rich solutions cause hyperchloraemic acidosis in a dose-dependent manner and induce a potassium shift to the extracellular space, thereby increasing serum potassium levels. Thus, balanced electrolyte solutions are to be preferred in this setting. Dogma #4 relates to the fact that enteral nutrition is often withheld for patients with high residual gastric volume due to the theoretical risk of gastro-oesophageal reflux, potentially resulting in aspiration pneumonitis. Despite controversial discussions, there is no clinical data supporting that residual gastric volume should be generally measured, especially not in patients without a gastro-intestinal surgery and/or motility disorders. Clinical evidence rather suggests that abandoning residual gastric volume monitoring does not increase the incidence of pneumonia, but may benefit patients by facilitating adequate enteral feeding. Finally, dogma #5 is about sedating all mechanically ventilated patients because “fighting” against the respirator may cause insufficient ventilation. This concern needs to be balanced against the unwanted consequences of sedation, such as prolonged mechanical ventilation and intensive care unit length of stay as well as increased risk of delirium. Modern concepts based on adequate analgesia and moderate to no sedation appear to be more suitable. In conclusion, dogmas are still common in clinical practice. Since science rather than fiction should govern our actions in intensive care medicine, it is important to remain critical and challenge long established concepts, especially when the underlying evidence is weak or non-existing.